Conductive-perovskite LaNiO3 Thin Films Prepared by Using Solution Process for Electrode Application - Hoa, Nguyen Quang; Trinh, Bui Nguyen Quoc (VNU Journal of Science: Mathematics - Physics, 2018)
Lanthanum nickel oxide LaNiO3 (LNO) isextensively known as one of typical perovskite-structured materials with metallic conductivity, which is suitable for the electrode application in electronic devices such as transistors or solar cells. Since LNO is a low-cost material and a simple fabrication process, it has been attracted much attention for commercialization. In this paper, we have focused on optimizing the fabrication process of LNO thin films on SiO2/Sisubstrate and Al foil by using asolution process. The crystal structure and surface morphology were characterized by using X-ray diffraction and field-emission scanning electron microscopy (FE-SEM), respectively. It was found that the LNO thin films annealed in range of 550-700oC for 30 minutes exhibited a well-formed crystallization and a dense microstructure. According to the SEM cross-sectional observation, the thickness of LNO thin films was estimated about 80 nm. Also, from the four-probe measurement method, the electrical resistivity of LNO thin film annealed at 600oC had a minimum value of 0.42× 10-2 Ωcm, which waspossibly comparable to conventional conductive oxides. As a result, thecapacitor using Pb1.2(Zr0.4Ti0.6)O3ferroelectric layer annealed at 600oC and LNO bottom electrode providedan interesting ferroelectricity, which includeda remnant polarization of 21µC/cm2 and a saturated polarization of 35µC/cm2 . Moreover, the leakage current density was lower than 2 × 10-5 A/cm2 . Keywords LNO, conductive perovskite,solution process, ferroelectric, PZT References [1] Y. Guo, D. Akai, K. Sawada, and M. Ishida, The performance of Pt bottom electrode and PZT films deposited on Al2O3/Si substrate by using LaNiO3 film as an adhesion layer, Solid State Commun., 145 (2008) 413-417. [2] Y. Zhu, H. Wang, P. Liu, W. Yao, and L. Cao, Preparation and conducting performance of LaNiO3 thin film on Si substrate, Thin Solid Films, 471 (2005) 48-52. [3] Z.Q. Hu, B. Ma, S. Liu, M. Narayanan, and U. Balachandran, Ceramic dielectric film capacitors fabricated on aluminum foils by chemical solution deposition, Mater. Res. Bull., 52 (2014) 189-193. [4] Y.S. Jeon, J.H. An, K.S. Hwang, B.A. Kang, and T. Tsuchiya, AFM study of LaNiO3 thin films on various single crystal substrates prepared by using a metal naphthenate precursor, Surf. Coat. Technol., 190 (2005) 331-335. [5] R.D. Sanchezm, M.T. Causa, A. Caneiro, and A. Butera, Metal-insulator transition in oxygen-deficient LaNiO3-x perovskites, Phys. Rev. B, 54 (1996) 16574-16578. [6] G. Gou, I. Grinberg, A.M. Rappe, and J.M. Rondinelli, Lattice normal modes and electronic properties of the correlated metal LaNiO3, Phys. Rev. B, 84 (2011) 144101. [7] A. Yu. Dobin, K.R. Nikolaev, I.N. Krivorotov, R.M. Wentcovitch, and A.M. Goldman, Electronic and crystal structure of fully strained LaNiO3 films, Phys. Rev. B, 68 (2003) 113408. [8] L. Sun, Y.F. Chen, and T. Yu, Conductive LaNiO3 electrode grown by pulsed laser ablation on Si substrate, J. Mater. Res., 12 (1996) 931- 935. [9] Q. Liu, G. Zhao, and L. Lei, Fabrication of LaNiO3 thin film on the Si- substrate by sol-gel process, Mater. Sci., 695 (2011) 529-532. [10] K. Sreedhar, J.M. Honig, M. Darwin, M. McElfresh, P.M. Shand, and J. Spalek, Electronic properties of the metallic perovskite LaNiO3: Correlated behavior of 3d electron, Phys. Rev. B Condens. Matter., 46 (1992) 6382-6386. [11] Y. Wang, G. Zhang, C. Li, G. Yan, and Y. Le, Preparation and characterization of LaNiO3 films grown by metal-organic deposition, Bull. Mater. Sci., 34 (2011) 1379-1383. [12] T. Yu, Y.F. Chen, Z.G. Liu, S.B. Xiong, L. Sun, X.Y. Chen, L.J. Shi, and N.B. Ming, Epitaxial Pb(Zr0.53Ti0.47)O3/LaNiO3 heterostructures on single crystal substrates, Appl. Phys. Lett., 69 (1996) 2092-2094. [13] K. Hwang, Y. Lim and B. Kim, Epitaxially grown LaNiO3 thin films on SrTiO3(100) substrates by the chemical solution method, Mater. Res. Bull., 34 (1999) 2069-2074. [14] T. Schneller, R. Waser, M. Kosec, and D. Payne, Chemical solution deposition of functional oxide thin films, Springer-Verlag Wien, New York (2013) 623. [15] B. Kaleli, M.D. Nguyen, J. Schitz, R.A.M Wolters and R.J.E Hueting, Analysis of thin-film PZT/LNO stacks on an encapsulated TiN electrode, Microelectron. Eng., 119 (2014) 16-19. [16] C.C. Yang, M.S. Chen, T.J. Hong, C.M. Wu, J.M. Wu and T.B. Wu, Preparation of (100)-oriented metallic LaNiO3 thin films on Si substrates by radio frequency magnetron sputtering for the growth of textured Pb(Zr0.53Ti0.47)O3, Appl. Phys. Lett., 66 (1995) 2643-2645.